2021
DOI: 10.3390/cancers13205073
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E Mutant Allele Frequency (MAF) Influences Melanoma Clinicopathologic Characteristics

Abstract: Background: Cutaneous melanoma shows high variability regarding clinicopathological presentation, evolution and prognosis. Methods: Next generation sequencing was performed to analyze hotspot mutations in different areas of primary melanomas (MMp) and their paired metastases. Clinicopathological features were evaluated depending on the degree of variation of the BRAFV600E mutant allele frequency (MAF) in MMp. Results: In our cohort of 14 superficial spreading, 10 nodular melanomas and 52 metastases, 17/24 (71%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…In addition, melanocytes from chronically sun-exposed areas (e.g., the face, neck, and bald scalp) displayed a lower mutational burden than melanocytes on intermittently exposed skin (e.g., the back and the limbs) [12]. This assertion mirrors the clinical observations that, compared to other forms of skin cancer, melanomas are more common in intermittently exposed skin than in chronically exposed skin [54][55][56].…”
Section: Discussionsupporting
confidence: 65%
“…In addition, melanocytes from chronically sun-exposed areas (e.g., the face, neck, and bald scalp) displayed a lower mutational burden than melanocytes on intermittently exposed skin (e.g., the back and the limbs) [12]. This assertion mirrors the clinical observations that, compared to other forms of skin cancer, melanomas are more common in intermittently exposed skin than in chronically exposed skin [54][55][56].…”
Section: Discussionsupporting
confidence: 65%
“…Results indicated that High-BRAFV600E MMp were all located on the trunk, had lower Breslow and mitotic indices, and were predominantly first nodal metastases. The high-BRAFV600E MMp patients had better prognostic features and first nodal metastasis ( 37 ). In the present study, we did not investigate whether the MAF of BRAF V600E potentially impacts the clinical outcome of NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%